THE ROLE OF HISTORY EDUCATION IN SHAPING THE CRITICAL AWARENESS OF GENERATION Z IN SENIOR HIGH SCHOOLS - Ernawati (SMART: Journal of Multidisciplinary Educational, 2024)
This study aims to examine how history education in senior high schools can foster critical awareness among Generation Z students by aligning pedagogical practices with their cognitive and digital characteristics. Employing a library research method, the study analyzed over 30 recent scholarly sources from the last five years, focusing on themes such as digital literacy, historical thinking, student engagement, and curriculum relevance. The findings indicate that while digital tool integration and interactive methods are frequently emphasized, their practical implementation remains inconsistent due to teacher readiness, curriculum constraints, and limited scaffolding for critical reflection. A major contribution of this research lies in its conceptual novelty: it bridges the domains of history education, Generation Z learning behavior, and digital pedagogical practices, offering a framework to interpret how these elements shape students' ability to question historical narratives and link past events to contemporary issues. Unlike previous studies that treat digital engagement or historical knowledge in isolation, this study synthesizes these dimensions into a unified approach to developing critical historical consciousness. The research also proposes a diagnostic model that can inform future empirical assessments and guide teacher professional development. In conclusion, this study highlights the urgent need for a transformative shift in history education toward inquiry-based, student-centered, and digitally responsive teaching. This shift is essential to empower Generation Z as reflective, analytical, and civically engaged citizens in a complex digital world.